Pengaruh Motivasi, Budaya, dan Sikap Konsumen Terhadap Keputusan Pembelian Produk Indomie - Keren, Keren; Sulistiono, Sulistiono (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
Consumption of instant noodle products in Indonesia is quite high. Especially the Indomie instant noodle which is the market leader in the Indonesian instant noodle product market. In purchasing products, consumers are influenced by three factors, namely motivation, culture, and consumer attitudes. This research is a survey research with data collection method through interviews using a questionnaire instrument to 100 respondents in the Bogor city. Based on the analysis of the data obtained, it is known that of the three variables studied, Consumer Attitude is the most influential variable on the Purchase Decision of Indomie brand instant noodle products because it has the greatest beta value among the other variables. From the partial test results (t and F test) it can be obtained that the three exogeneus variables (Consumer Motivation, Culture, and Consumer Attitudes) have the same strong and positive influence simultaneously on the Purchase Decision of Indomie brand instant noodle products.